Epistemological belief and learning approaches of students in higher institutions of learning in Malaysia - Ismail, Habsah; Hassan, Aminuddin; Muhamad, Mohd Mokhtar; Wan Ali, Wan Zah; Konting, Mohd Majid (Faculty of Education, Eskisehir Osmangazi University, 2013)
This is an investigation of the students’ beliefs about the nature of knowledge or epistemological beliefs, and the relation of these beliefs on their learning approaches. Students chosen as samples of the study were from both public and private higher institutions of learning in Malaysia. The instrument used in the study consists of 49 items measuring students’ epistemological beliefs and 20 items on their learning approaches. Items on epistemological belief were adapted and modified from Schommer’s Epistemological Questionnaire (1990) and Schraw, Bendixen and Dunkle (2000) Epistemic Beliefs Inventory that assesses students' beliefs about simple knowledge, certain knowledge, quick learning, and fixed ability to learn. Items on learning approaches were adapted from Bigg’s forty-two-item Study Process Questionnaire (SPQ), designed for tertiary-level students. The instrument was administered to 1405 students of higher institutions of learning both public and private. Differences in epistemological beliefs among students of these higher institutions, ethnic and between genders were examined.